2015
DOI: 10.1111/nph.13341
|View full text |Cite
|
Sign up to set email alerts
|

Blue‐light dependent reactive oxygen species formation by Arabidopsis cryptochrome may define a novel evolutionarily conserved signaling mechanism

Abstract: SummaryCryptochromes are widespread blue-light absorbing flavoproteins with important signaling roles. In plants they mediate de-etiolation, developmental and stress responses resulting from interaction with downstream signaling partners such as transcription factors and components of the proteasome. Recently, it has been shown that Arabidopsis cry1 activation by blue light also results in direct enzymatic conversion of molecular oxygen (O 2 ) to reactive oxygen species (ROS) and hydrogen peroxide (H 2 O 2 ) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 103 publications
(89 citation statements)
references
References 38 publications
5
83
0
1
Order By: Relevance
“…1K and L). Atcry2 nuclear localization has also been confirmed by nuclear 3D analysis as described previously 3 (data not shown). It is therefore evident that cry2 undergoes lightdependent translocation into the nucleus in this heterologous insect cell culture system, somewhat in contrast to what has been reported in plants.…”
Section: Atcry2 Is Translocated Into the Nucleus In A Bluelight Depensupporting
confidence: 75%
See 4 more Smart Citations
“…1K and L). Atcry2 nuclear localization has also been confirmed by nuclear 3D analysis as described previously 3 (data not shown). It is therefore evident that cry2 undergoes lightdependent translocation into the nucleus in this heterologous insect cell culture system, somewhat in contrast to what has been reported in plants.…”
Section: Atcry2 Is Translocated Into the Nucleus In A Bluelight Depensupporting
confidence: 75%
“…In our original study 3 and in this accompanying manuscript, we have shown a potentially novel way in which cryptochromes may participate in signaling. Whereas there is convincing evidence that conformational changes induced by primary photochemical events lead to interaction with cry signaling partners, this does not exclude that formation of ROS may also play a role in cryptochrome signaling.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations